1996
DOI: 10.1103/physrevlett.77.1994
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and Anchoring of a Nematic Liquid Crystal on a Rough Surface

Abstract: Ellipsometric measurements of a nematic drop spreading on a rough surface are reported. The thickness profile of the drop shows two typical lengths belonging to the microscopic and to the mesoscopic scales (a few tens and some hundreds of Å, respectively). No intermediate thicknesses are observed during the spreading. A simple model involving the balance among elastic, anchoring, and spreading energies is used to interpret the results. [S0031-9007(96)00975-1] 68.45.Gd Nematic liquid crystals (NLC) are unia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 14 publications
6
83
0
1
Order By: Relevance
“…This elastic energy is stored in intermolecular distances and orientations that are stretched or compressed from the bulk values by the influence of the substrate at short distances (Valignat et al, 1996). Similar phenomena are well known to occur in the growth of epitaxial layers in metals and semiconductors.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This elastic energy is stored in intermolecular distances and orientations that are stretched or compressed from the bulk values by the influence of the substrate at short distances (Valignat et al, 1996). Similar phenomena are well known to occur in the growth of epitaxial layers in metals and semiconductors.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, these interesting liquids provide a good testing ground for fundamental theories of wetting. Films of 8CB (4'-n-octyl-4-cyanobiphenyl) have been studied by optical microscopy, X-ray reflectivity (Bardon et al, 1999;Pershan, 1989), ellipsometry (Valignat et al, 1996;Bardon et al, 1999), second-harmonic generation (Feller et al, 1991), scanning tunneling microscopy (STM) (Stevens et al, 1998), AFM (Fang et al, 1997), and SFA (Artsyukhovich et al, 1999).…”
Section: Layering Of Liquid Crystalsmentioning
confidence: 99%
“…The competition of attractive van der Waals forces and short range repulsive forces, like Born repulsion, can produce complex instabilities in layers of thin liquid films on solid substrates. Experimental studies have shown this behavior for polymer films [66,81,87,88,101], liquid crystal films [58,93,94], liquid metals [29,58] and evaporating films [41,76]. During these dewetting processes, large droplets are formed which are connected by ultra-thin films.…”
Section: Dewetting Filmsmentioning
confidence: 99%
“…The LC droplet thereby experiences anchoring at two separate interfaces: LC-solid interface and LC-air interface. Given that the nematic anchoring at LC-air interface is typically homeotropic [177][178][179], the overall director field within the droplet is essentially determined by the boundary conditions at the solid substrate. For instance, if the solid substrate possesses uniform planar anchoring, then the director field is expected to equilibrate to a hybrid-aligned configuration (Section 4.…”
Section: Liquid Crystals In Confinementsmentioning
confidence: 99%